Metapher, Allegorie, Symbol - Kurz, Gerhard 1943- (Göttingen Vandenhoeck u. Ruprecht, 1988)
Literaturverz. S. 94 - 103
Literaturverz. S. 94 - 103
Archivierung/Langzeitarchivierung gewährleistet
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Metapher; Allegorie; Symbolik